Research on Yoga for stress management: Bibliometric trends from 2000 to 2024 - Juhi Kumawat; Kashinath G. Metri (Journal of Ayurveda and Integrative Medicine)
Background: Yoga has emerged as a widely recognized intervention for managing stress, with growing interest in its effectiveness across various populations. Despite expanding research, there remains a need for comprehensive analysis of trends within the literature to guide future studies and clinical applications. Objective: This study aimed to analyze bibliometric trends in research on yoga for stress management, providing insights into publication patterns, key contributors, and evolving research directions in this field. Methods: The experimental studies related application of yoga for stress management were searched from 2000 to 2024 on Scopus database. The search criteria were refined to include publications on yoga related to stress, with a focus exclusively on articles published in English. Quantitative data analysis was conducted using bibliometric tools, with visualizations created using VOSviewer. Results: The analysis of 1025 articles revealed a significant increase in publications over 24 years, especially in the past four years. The International Journal of Yoga Therapy and the Journal of Alternative and Complementary Medicine were leading journals in this field. The United States and India were identified as primary contributors, with Khalsa SBS and Nagendra HR being the most prolific authors. Randomized controlled trials, meta-analyses, and systematic reviews emerged as predominant study types. Conclusion: This comprehensive bibliometric analysis highlights the growth of yoga and stress management research, emphasizing randomized controlled trials and evidence-based practices. Future studies should explore yoga’s impact on diverse populations by age, occupation, and culture to clarify its universal applicability, advancing research and clinical applications.